Pengaruh Terapi Relaksasi Otot Progresif Terhadap Kualitas Tidur Lansia Di Desa Fajar Kecamatan Sorkam Kabupaten Tapanuli Tengah Tahun 2021 - Vivi Florensia; Anggriani Anggriani; Liza Agustin (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Elderly age (elderly) is the final period in human life marked by psychological-social changes and physical changes resulting in decreased weakness, increased susceptibility to disease, and physiological changes, namely with disturbances to the sleep quality of the elderly. Poor sleep quality in the elderly is caused by increased sleep latency, reduced sleep efficiency, and early awakening due to the aging process. Treatment of sleep disorders can use complementary therapies, one of which is progressive muscle relaxation therapy. The purpose of this study was to identify whether there is an effect of progressive muscle relaxation therapy on sleep quality in the elderly. This research was conducted on 19-26 August 2021, this study used a research one group pre-post test design with a sampling technique using purposive sampling. The population in this study were the elderly in Fajar Village, Sorkam District, Central Tapanuli Regency, totaling 30 people aged 60-74 years, female, elderly who are no longer actively working, can see and hear and have light/moderate/poor sleep quality. . This study used the SOP for progressive muscle relaxation therapy and the Pittsburgh sleep quality index (PSQI) questionnaire. By using the method Wilcoson Sign Rank Test, the p-value is 0.000 (p<0.05). Based on the results of the study, there was an effect of progressive muscle relaxation therapy in the elderly in Fajar Village, Sorkam District, Central Tapanuli Regency with a pre-post value, with p<0.05 (0.000). Thus, it can be expected that people with sleep quality disorders should apply progressive muscle relaxation therapy to reduce sleep quality, especially in Fajar Village, Sorkam District, Central Tapanuli Regency. Keywords: Progressive muscle relaxation, sleep quality, the elderly